PEMANFAATAN KITOSAN DARI KULIT UDANG UNTUK MENURUNKAN KADAR PENCEMAR ORGANIK LIMBAH CAIR KELAPA SAWIT - Michelle Clara Sinabariba; Didi Jaya Santri; SB, Susy Amizera (Edumedia : Jurnal Keguruan dan Ilmu Pendidikan, 2025)
This study aims to find out how effective chitosan formulation is in reducing the level of organic pollutants of palm oil liquid waste and the amount of effective doses of chitosan to reduce the level of organic pollutants of liquid waste. This research was carried out from September 2024 to July 2025 at the Biology Education Laboratory, Sriwijaya University. This study is a type of experimental quantitative research using a Complete Random Design (RAL) with 5 treatments and 5 replicates with a exposure time of 5 days. The data from the study were analyzed using homogeneity tests, normality tests, fingerprint tests (ANOVA) and Duncan Multiple Range Test (Duncan) tests with observed parameters, namely pH, DO, TDS, TSS, and COD. The results showed that giving 1 gram of shrimp skin chitosan was able to raise the pH by 59.74% with an average pH of 7.38. Treatment 1 using 0.5 grams of shrimp skin chitosan was able to reduce TDS levels by 72.5% to 605 mg/l. The administration of chitosan as much as 2 grams was able to improve the parameters of wastewater quality with an average change of TSS of 98.82% to 3000 mg/l, COD of 94.44% to 124.67 mg/l, DO value decreased by 10% to 0.72 mg/l. Based on the results of the analysis, it can be concluded that shrimp skin chitosan is able to become a natural coagulant to reduce the level of organic pollutants of palm oil liquid waste. The results of this study were contributed in the form of LKPD Environmental Change material for high school grade X students (phase E). Keywords : Chitosan Shrimp Shell, Liquid Waste, Oil Palm, Organic Pollutants